Electrical conductivity of barium substituted LSGM electrolyte materials for IT-SOFC - Raghvendra; Singh R.K.; Singh P. (My University, 2025)
Strontium and magnesium doped lanthanum gallate, La0.9Sr 0.1Ga0.8Mg0.2O2.85 (LSGM), and Ba-incorporated LSGM with compositions La0.9 - xBaxSr 0.1Ga0.8Mg0.2O2.85; x ≤ 0.15 (LBSGM) were prepared by conventional solid state route. The X-ray diffraction patterns of the LBSGM system showed the main orthorhombic LSGM phases along with a few impure secondary phases. SEM micrographs exhibited fairly densed grain morphology of the system. The XPS spectra of the system indicated the presence of the constituent elements. It was found that sintered samples are stable in air and the constituent elements were found to exist in their characteristic valence states. The electrical conductivity of the LBSGM system was measured in the frequency range 20 Hz to 1 MHz and a temperature range of 300-800 °C. The electrical conductivity of the system was found to increase slightly first up to x = 0.07 and thereafter it decreased for higher dopant concentrations. The formation of additional Ba-derived secondary phases in the compositions with x > 0.07 may lead to a decrease in electrical conductivity. © 2014 Elsevier B.V.